Strategi Integrasi Sirkuit Mandalika dan Olahraga Tradisional untuk Meningkatkan Daya Saing Destinasi Wisata Sport Tourism - Amin Pujiati; Sucihatiningsih Dian Wisika Prajanti; Jumesam Jumesam; Suryansah Suryansah; Aristiyanto Aristiyanto; Guntur Ratih Prestifa Herdinata; Fredy Eko Setiawan; Muhammad Syaleh; Dixon E. M. Taek Bete (Jurnal Porkes, 2025)
The construction of the Mandalika Circuit has positioned Lombok as a global sports tourism destination, particularly in the field of motorsports. However, sustainable competitiveness requires irreplaceable uniqueness. Traditional sports such as Presean and Bau Nxale (a maritime tradition with a sporting element), as well as Perahu Bedar, are cultural assets with high commercial value. The integration of the modern image of the Mandalika Circuit and the authenticity of traditional sports has the potential to create a Unique Selling Proposition (USP) for Lombok. This study aims to formulate a strategy for integrating these two elements to create a comprehensive sports tourism package. A qualitative method with case studies was used, with data collected through in-depth interviews with relevant stakeholders and analyzed using SWOT. The results of the study identify a great opportunity for a “Dual Experience: Adrenaline & Culture” package. The circuit serves as an anchor attraction, while traditional sports become a complementary product that extends the length of stay and increases tourist spending. The key to the success of this strategy lies in integrated marketing, professional event management, and authentic tourism experience packaging.